A new lightweight masonry block: Thermal and mechanical performance - Luísa Costa Sousa (2014)
The concerns with masonry building envelope performance, particularly thermal efficiency, are causing major changes in masonry solutions, mainly in south European countries, where traditionally the mild winter climate justified the use of high thermal masonry wall performance. The new European Directives regulations require different solutions. This paper describes the development a new masonry system, based on lightweight concrete units, intended for construction of large single leaf external walls without thermal insulation materials. A detailed analysis and optimization has been performed by FEM, under thermal point of view. This work was followed by a set of experimental tests in order to characterize the mechanical behavior of single units and masonry specimens. The concerns with productivity and ergonomics are also considered according their importance to the solution cost.